ANALISIS YURIDIS AKIBAT HUKUM PERJANJIAN BAGI HASIL TANAH PERTANIAN YANG DILAKUKAN TIDAK TERTULIS BERDASARKAN UU NO. 2 TAHUN 1960 - SANIAH . (LP2MTBM MAKARIOZ, 2020)
The objective of this research is to find out the legal consequences of an unwritten agreement for agricultural landproduction. This research is a normative legal research. The yuridical sources were primary, secondary and tertiary lagalmaterials.The data were gathered by conducting documentary study. The conclution of the research is that Law No. 2 of1960 does not regulate the legal consequences if the agreement between the land owner and the tenant is made unwriting.